THE EFFECTS OF THE FIREARM PURCHASINGS ON THE OTTOMAN FINANCIAL STRUCTURE DURING THE MILITARY MODERNIZATION (1853-1908) - Karakoc, Ercan; Mete, Ali Serdar (SELCUK UNIV, INST TURKISH STUDIES, 2020)
Reforms implemented for the Ottoman army began to be institutionalized in the middle of the 19th century. The basic idea was to restore the former power of the army. Since the changing conditions of war had shown that reform was possible only with the application of modern methods to every field, the works made on the modernization of the Ottoman army gained momentum after the Crimean War. The effort to establish an army in-line with the requirements of modern warfare was the Ottoman administration's primary aim during the Reorganization and Constitutional periods. The provision of resources required to sustain military modernization led to different measures in the Ottoman economy such as domestic and foreign borrowing, interest postponement, transfer of revenues, and ultimately the allocation of revenues to creditors. In this process, while the Ottoman economy became integrated into the international economy, it gradually became dependent on foreign sources. Despite the economic measures taken did not reduce dependency on international resources and the heavy financial burden, the Ottoman administration sustained military reforms and modernization.
Keywords: Modern Warfare; Crimean War; Military Modernization; Ottoman Economy; Arts & Humanities - Other Topics